Investment strategies for retirement - Nicolas, Franck (World Scientific Publising Co Pte Ltd., 2018)
The issue of pension financing is evolving everywhere, becoming more of a corporate or individual matter rather than a state one. Demographic changes are making sharing mechanisms hard to control, and social deficits often lead governments to pull back from their obligations. This raises many questions for the individual: At what age should I start saving? When should I increase or reduce my savings? How do I secure my income? What products should I choose to supplement my pension and savings? What degree of risk should I take on? Despite the burden for securing one's retirement increasingly placed on individuals, many are often badly prepared to tackle this very long savings process, which is often complicated by the specific characteristics of a pension plan. This publication, intended for investment professionals, customer advisors, and individuals interested in personal finance and asset management, looks at some of the fundamental elements of investment strategies and techniques for retirement